Child Injury and the Determinants of Health - Peden, Amy; Franklin, Richard (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The World Health Organization recognizes that injuries are the leading cause of death and disability to children after their first birthday. There is also high morbidity associated with injuries sustained in childhood, often affecting people for the rest of their lives. For every child who dies from injury, there are several thousand who require medical care, many who live with varying degrees of disability. Children and adolescents (0-19 years of age) are at increased risk of mortality and morbidity due to injuries such as road traffic, burns, falls, poisoning, drowning, self-harm and interpersonal violence. There are proven ways to prevent many child injuries, yet there are still gaps in our knowledge. By understanding the impact of determinants of health (i.e., the social and economic environment, the physical environment and a person's individual characteristics and behaviors), effective prevention interventions can be designed and implemented, with a high return on investment. This Special Issue covers an eclectic range of studies, the common goal of which is to reduce the global burden of child injury-related mortality and morbidity.